Indice de aminoácidos libres y estructuras celulares como indicadores de calidad en jugos de fruta - Rumiche B., Jesús (2000)
Two parameters not considered as paradigms for quality control of natural fruit juice in the Peruvian Technical Norms are studied here. These parameters a) free amino acid index (FAI) and b) ceIlular structures (CE), would contribute with quantitative and qualitative data to evidence genuinely and quality. In 11 juices prepared at lab level according to pH, acidity and soluble solids specifications and of high consume (peach, strawberry, mandarin orange, mango, apple, maracuya, orange, melon, pear, pineapple and grape) it has been determined: A) the microscopic cellular characteristics (WaIlis metbod) and b) free amino acid index, by means of the formalin index (an A.O.A.c. official method). The same parameters were analyzed in 18 rmnufactured tradermrk juices that are commercialized in the country. This result is reported graphically in photographs taken at tbe moment of CE microscopic observation and values reported in tables submitted to statistical analysis. These ones indicate that the formalin index, expressed as a free amino acid index in the presence of cellular structures, is independent (r= 0,2587) and tbat in absence of cellular structures, the free amino acid index acquires a confirmative character about the genuinely of the raw materials employed in juice manufacture. In manufactured juices, quantifiable amounts of aminic nitrogen are reported, although these values are below tbe ones obtained with laboratory prepared fruit juices.